2002
DOI: 10.1111/1469-7610.00082
|View full text |Cite
|
Sign up to set email alerts
|

Teen‐aged mothers in contemporary Britain

Abstract: Young mothers today face difficulties known to have long-lasting effects for women and their children. Preventions that target young mothers may reduce harm to the physical health, mental health, and social status of future generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
316
2
7

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 390 publications
(339 citation statements)
references
References 73 publications
7
316
2
7
Order By: Relevance
“…The E-risk sample was constructed in 1999 -2000, when 1,116 families with same-sex 5-year-old twins (93% of those eligible) participated in homevisit assessments, forming the base cohort for the longitudinal E-risk study. Details about the sample are reported elsewhere (50). Because each study family contains two children, all statistical analyses reported here were corrected conservatively for the nonindependence of the twin observations by using tests based on the sandwich or Huber/White variance estimator (51).…”
Section: Methodsmentioning
confidence: 99%
“…The E-risk sample was constructed in 1999 -2000, when 1,116 families with same-sex 5-year-old twins (93% of those eligible) participated in homevisit assessments, forming the base cohort for the longitudinal E-risk study. Details about the sample are reported elsewhere (50). Because each study family contains two children, all statistical analyses reported here were corrected conservatively for the nonindependence of the twin observations by using tests based on the sandwich or Huber/White variance estimator (51).…”
Section: Methodsmentioning
confidence: 99%
“…Age at first childbearing was used as the riskstratification variable because it was recorded for virtually all families in the register, it is relatively free of measurement error, and early childbearing is a known risk factor for children's problem behaviors. 26,27 The sampling strategy resulted in a final sample in which one-third of Study mothers (younger only; N = 314) constitute a 160% oversample of mothers who were at high risk based on their young age at first birth (15-20 years). The other two-thirds of Study mothers (N = 802) accurately represent all mothers in the general population (aged in England and Wales in 1994-1995 (estimates derived from the General Household Survey 28 ).…”
Section: Samplementioning
confidence: 99%
“…In this case, the link between externalizing behavior and CUD is due to other factors (confounders), rather than causal. For example, child and adolescent externalizing behaviors are associated with teenage motherhood, marital disruption, poor maternal mental health, maternal substance use, low socio-economic status, poor family functioning, and parental supervision of the child ( [Moffitt, 2002b], [Moffitt, 2006], [Nagin and Tremblay, 2001] and [Weissman et al, 1999]). These family factors are also associated with the later use of substances by children ( [Hawkins et al, 1992] and [Hayatbakhsh et al, 2006]).…”
Section: Introductionmentioning
confidence: 99%